Rice Ecosystem, Allelopathy and Environment A Review - Siddique, AB; Ismail, BS (The Agriculturists, 2013)
Allelopathy is an important factor which contributes in determining distribution of species and their abundance within communities. Plant-plant interference is the combined effect of allelopathy, resource competition, and many other factors. Weed infestation is a major problem limiting the growth and yield of rice. Synthetic herbicide has been used for over 50 years as the prime source of weed control. The repeated use of herbicides in rice has already led to the evolution of resistance in some weed species. The conventional synthetic herbicides are becoming less effective against the resistant weed biotypes. Due to increase in the number of herbicide-resistant weeds and environmental concerns in the use of synthetic herbicides, allelopathy has been gaining preference as one of the considerable efforts in designing alternative weed management strategies. Modern ecotoxicologists and allelopathy researchers have been trying to identify allelochemicals to use as biodegradable pesticide. Two allelochemicals have been discovered, namely hexanedioic acid dioctyl ester and di-n-octyl phthalate which can be used as biopesticide. However, still there is enough scope to conduct such research that will contribute to protect our environment as well as increase food safety. DOI: http://dx.doi.org/10.3329/agric.v11i1.15251 The Agriculturists 2013; 11(1) 112-121